Diseño de un sistema fotovoltaico para satisfacer la demanda de energía eléctrica de la granja avícola “GRAVIPAL” ubicada en el cantón Palanda de la provincia de Zamora Chinchipe. - Pinta Seminario, Jhon Michael (2022)
The present thesis project tells about the design of a solar photovoltaic system, which is for the supply of the GRAVIPAL poultry farm, located in Palanda Zamora Chinchipe• Ecuador. This farm is about 215m2, on the surface, with 5 sheds of 40 m2 each one, and a pantry of 15 m2. The power needed for this farm represents the electrical power of two illumination circuits of 30 lux. A number is given by Aviagen (2019) for each shed. Each circuit is 54 watts and 45 watts respectively. In addition, it was also designed a supply and a circuit for water pomp of 373 watts. Being the total power supply 1590.5 Wh each day. On the other hand, the power needed begins with the solar influence ratio on the site, which is 3.15 kWh/m2day. All this information was given by the Universidad Nacional de Loja website. So, in the end, the system counted on 7 solar panels of 230 Wp each, 4 batteries of 250 Ah, 2 current regulators of 50 A, and a current inverter of 500 W. Finally, the system reached 78.9% efficiency, with an inclination angle for the panels of 6. 72 degrees. In addition, the cables were designed taking the National Electric Code. In the end, a unit cost analysis was also made, giving approximately the cost for the construction of the system, as well as the mechanical and electrical drawings, for more detail. Keywords: solar system, panels, shed, water pump, solar electric demand, design, implementation